KEMAMPUAN VISUAL-SPATIAL THINKING DALAM GEOMETRI RUANG MAHASISWA UNIVERSITAS KUNINGAN - Sumarni Sumarni; Anggar Titis Prayitno (Department of Mathematics Education, Universitas Kuningan, 2016)
AbstractÂ Geometry is a branch of mathematics that is taught in school, from elementary school, high school and college. Student Mathematics Education Kuningan University in the course Geometry 3D which gained less than satisfactory achievements in the course of the geometry 3D. The ability visual thinking and spatial thinking affect learners' achievements in learning the geometry. Authors interested in diagnosing the difficulties Student Mathematics Education of Kuningan University in the course Geometry 3D through Ability Test of Visual-Spatial Thinking. The purpose of this study is to diagnose visual-spatial thinking abilities Student of Kuningan University and describe efforts to improve student results in the course of the geometry 3D. Based on the exposure of the work about the ability of visual-spatial thinking and discussion it can be concluded that: a) The ability of visual-spatial thinking mathematics education student Kuningan University is still low, especially students who are capable of moderate and low. Students are still experiencing difficulties in resolving problems related to the concept of a perpendicular line and projections; distance of points, lines and areas; as well as the angle between the line and the field; b) The ability of visual-spatial thinking is a skill that must be developed in studying the geometry 3D, one of the low result of learning the geometry 3D is due to the ability of visual-spatial thinking is still low; c) One effort to improve visual-spatial thinking ability of students is learning the geometry of space through problem-based learning with assisted software GeoGebra.Keywords: Visual-Spatial Thinking Ability, Geometri 3D